2021
DOI: 10.1186/s12950-021-00289-1
|View full text |Cite
|
Sign up to set email alerts
|

Bullatacin triggers immunogenic cell death of colon cancer cells by activating endoplasmic reticulum chaperones

Abstract: Background It is well accepted that the immune system efficiently contributes to positive outcomes of chemotherapeutic cancer treatment by activating immunogenic cell death (ICD). However, only a limited number of ICD-inducing compounds are well characterized at present; therefore, identification of novel ICD inducers is urgently needed for cancer drug discovery, and the need is becoming increasingly urgent. Methods Herein, we assessed the antitumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The components of the ER stress mechanism may constitute clinically relevant drug trigger ICD, which releases vital immune stimuli or danger signs that ultimately drive effective antitumor immunity 28,29 . Several recent studies also reported that DAMPs exposure or release, such ATP, HMGB1, and CRT from cancer cells is associated with occurrence of ICD 30 . To clarify whether LCD could induce ICD response in cervical cancer cells, we analyzed the expression of CRT and HMGB1 using western blotting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The components of the ER stress mechanism may constitute clinically relevant drug trigger ICD, which releases vital immune stimuli or danger signs that ultimately drive effective antitumor immunity 28,29 . Several recent studies also reported that DAMPs exposure or release, such ATP, HMGB1, and CRT from cancer cells is associated with occurrence of ICD 30 . To clarify whether LCD could induce ICD response in cervical cancer cells, we analyzed the expression of CRT and HMGB1 using western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…28,29 Several recent studies also reported that DAMPs exposure or release, such ATP, HMGB1, and CRT from cancer cells is associated with occurrence of ICD. 30 To clarify whether LCD could induce ICD response in cervical cancer cells, we analyzed the expression of CRT and HMGB1 using western blotting. The results revealed the expression of CRT was increased in HeLa and C-33A cells after LCD treatment.…”
Section: Lcd Induces Icd In Vitromentioning
confidence: 99%
“…Huang et al demonstrated that the latter could elicit surface exposure of CALR and enhance the efficacy of neoadjuvant chemoradiotherapy (CRT) in BALB/c mice inoculated with CT26 mouse colon carcinoma cells; in fact, the complete response rate in the lipotecan-based CRT group was higher than that of the 5-fluorouracil-based CRT group (33.3 vs. 16.7%, respectively). These findings suggest that lipotecan could become part of neoadjuvant CRT in CRC and improve clinical outcomes in a setting in which recurrence rates are still relevant (5-15% at 5 years) [35,36].…”
Section: Icd In Colorectal Cancermentioning
confidence: 88%
“…There is a clear need for novel therapeutics in colorectal cancer and high-throughput screening and validation platforms with a focus on harnessing ICD are essential. Recently, multiple agents have been identified as potential ER stress targeted therapies including ceapins (pyrazole amide ATF6 activators), HHQ-4 and plumbagin (GPR78 inhibitors), GSK2606414 and GSK2656157 (ATP-competitive PERK kinase inhibitors), and bullatacin with promising pre-clinical data emerging [ 42 47 ].…”
Section: Icd Inducers In Colorectal Cancermentioning
confidence: 99%